Climate for change : non-state actors and the global politics of the greenhouse - Newell, Peter (Cambridge University Press, 2013)
"Climate for Change: Non-state Actors and the Global Politics of the Greenhouse provides a challenging explanation of the forces that have shaped the international global warming debate. Unlike existing books on the politics of climate change, this book concentrates on how non-state actors, such as scientific, environmental and industry groups, as opposed to governmental organisations, affect political outcomes in global fora on climate change. It also provides insights into the role at the media in influencing the agenda." "The book will be of interest to all researchers and policy makers associated with climate change, and will be used in university courses in international relations, politics and environmental studies."